Using existing surveillance infrastructure to monitor pedestrians on pedestrian bridges: a proof of concept - Van der Merwe, Hardy Fraser (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.